Depression in a Depressed Area: Deservingness, mental illness, and treatment in the contemporary rural U.S. - Snell-Rood, Claire (Soc Sci Med, 2018)
People with mental illness face public scrutiny that provokes questions about their ability to cope, membership in society, and entitlement to state support. Less attention has been focused on how such scrutiny occurs at the community level, particularly when shared economic distress has generated a high burden of poor mental health. We employ theorizations of health-related deservingness to examine the local moral economies through which residents of an economically depressed area question who deserves to be depressed, how those with depression should cope, and what forms of treatment are sincere. Drawing on a multi-phase study (2014–2016) in Appalachian Kentucky, we analyze interviews conducted with women with depression and the health practitioners who work with them. In the rural U.S., the dim economy and scarce healthcare resources are attributed to exclusion from broader society. Naturalized as a moral response for enduring dead-end jobs and poverty, participants described how depression coping can positively demonstrate individuals’ commitment to providing for their families and mobility. However, when individuals are perceived to use depression diagnoses to access state entitlements or obtain medication as a “quick fix” that facilitates substance use, area residents question the veracity of symptoms and argue that treatment-seeking is insincere. In this way, rural moral concepts about work, entitlement, and self-sufficiency become embedded in contemporary ideas about mental health and its treatment. The tempered normalization of depression may offer possibilities for decreasing stigma and engendering conversations about patterned exclusions of rural Americans from broader U.S. prosperity. However, tense moral meanings about depression coping reveal both deepening and emergent social inequalities within rural communities. Attending to local moral economies that shape mental health deservingness is critical to understanding the complex overlaps and intersections between state, community, and family discourses.